Minimum wages and employment - David Neumark; William Wascher (Institute for the Study of Labor (IZA), 2007)
We review the burgeoning literature on the employment effects of minimum wages - in the United States and other countries - that was spurred by the new minimum wage research beginning in the early 1990s. Our review indicates that there is a wide range of existing estimates and, accordingly, a lack of consensus about the overall effects on low-wage employment of an increase in the minimum wage. However, the oft-stated assertion that recent research fails to support the traditional view that the minimum wage reduces the employment of low-wage workers is clearly incorrect. A sizable majority of the studies surveyed in this monograph give a relatively consistent (although not always statistically significant) indication of negative employment effects of minimum wages. In addition, among the papers we view as providing the most credible evidence, almost all point to negative employment effects, both for the United States as well as for many other countries. Two other important conclusions emerge from our review. First, we see very few - if any - studies that provide convincing evidence of positive employment effects of minimum wages, especially from those studies that focus on the broader groups (rather than a narrow industry) for which the competitive model predicts disemployment effects. Second, the studies that focus on the least-skilled groups provide relatively overwhelming evidence of stronger disemployment effects for these groups.
urn:nbn:de:101:1-20080425257
Keywords: 330; Mindestlohn; Beschäftigung; Ungelernte Arbeitskräfte; OECD-Staaten; USA